2008
DOI: 10.1073/pnas.0803611105
|View full text |Cite
|
Sign up to set email alerts
|

PIF1 directly and indirectly regulates chlorophyll biosynthesis to optimize the greening process in Arabidopsis

Abstract: Plants depend on light signals to modulate many aspects of their development and optimize their photosynthetic capacity. Phytochromes (phys), a family of photoreceptors, initiate a signal transduction pathway that alters expression of a large number of genes to induce these responses. Recently, phyA and phyB were shown to bind members of a basic helix-loop-helix family of transcription factors called phy-interacting factors (PIFs). PIF1 negatively regulates chlorophyll biosynthesis and seed germination in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
245
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 220 publications
(260 citation statements)
references
References 35 publications
(73 reference statements)
12
245
1
2
Order By: Relevance
“…Microarray studies using dark-grown single mutants for PIF3 (Monte et al, 2004;Leivar et al, 2009;Sentandreu et al, 2011) or PIF1 (Moon et al, 2008), and double mutants for PIF4 and PIF5 , showed relatively modest contributions of individual PIFs in regulating gene expression genome wide, consistent with the absence of robust morphological phenotypes of these mutants in the dark due to genetic redundancy (Leivar et al, 2008b(Leivar et al, , 2012bShin et al, 2009). In sharp contrast, the transcriptomic profile of pifq mutants in the dark largely resemble that of wild-type seedlings grown in the light (Leivar et al, 2009;Shin et al, 2009).…”
Section: Deetiolationmentioning
confidence: 78%
See 2 more Smart Citations
“…Microarray studies using dark-grown single mutants for PIF3 (Monte et al, 2004;Leivar et al, 2009;Sentandreu et al, 2011) or PIF1 (Moon et al, 2008), and double mutants for PIF4 and PIF5 , showed relatively modest contributions of individual PIFs in regulating gene expression genome wide, consistent with the absence of robust morphological phenotypes of these mutants in the dark due to genetic redundancy (Leivar et al, 2008b(Leivar et al, , 2012bShin et al, 2009). In sharp contrast, the transcriptomic profile of pifq mutants in the dark largely resemble that of wild-type seedlings grown in the light (Leivar et al, 2009;Shin et al, 2009).…”
Section: Deetiolationmentioning
confidence: 78%
“…The defined binding sites for these PIFs are located predominantly in promoter regions of target genes and are strongly enriched in the DNA motif G-box (CACGTG) and the E-box variant (CACATG and CATGTG) that has been called the PBE-box (for PIF binding E-box), suggesting that these PIFs have similar sequence recognition requirements in terms of DNA binding (Hornitschek et al, 2012;Oh et al, 2012;Zhang et al, 2013). In vitro assays have shown specific binding to the G-box for all the PIFs tested (PIF1, PIF3, PIF4, PIF5, and PIF7) (Martínez-García et al, 2000;Huq and Quail, 2002;Leivar et al, 2008a;Moon et al, 2008;Hornitschek et al, 2009) and to the PBE-box for PIF1, PIF3, and PIF4 (Kim et al, 2008;Hornitschek et al, 2012;Zhang et al, 2013).…”
Section: Deetiolationmentioning
confidence: 99%
See 1 more Smart Citation
“…2; Shi et al, 2013;Lee et al, 2015). PIF1 also regulates chlorophyll biosynthesis and plastid development by modulating the expression of a number of genes Moon et al, 2008;Kim et al, 2016c). PIF2 (more commonly known as PIL1) also interacts with COP1 and phyB in vivo ( Fig.…”
Section: Distinct and Shared Biological Functions Of Pifs In Arabidopsismentioning
confidence: 99%
“…The qRT-PCR was performed as previously described (Kim and Sung, 2010;Moon et al, 2008). Briefly, apical tissues including meristem were harvested from 60-day-old wt and nfl mutant plants grown under SD conditions at T0 ( just prior to turning on light at dawn) and total RNA was isolated as described above.…”
Section: Quantitative Rt-pcr Analysesmentioning
confidence: 99%